Effect of raw material and starters on the metabolite constituents and microbial community diversity of fermented soy sauce. (22nd August 2019) - Liang, Ru; Huang, Jun; Wu, Xueming; Fan, Jun; Xu, Yi; Wu, Chongde; Jin, Yao; Zhou, Rongqing
Abstract: BACKGROUND: The quality of soy sauce is strongly affected by microorganisms and raw materials (defatted soybean or whole soybean). The present study investigated the effect of two types of fortified pattern, including inoculation with starters ( Tetragenococcus halophilus combined with Zygosaccharomyces rouxii and Candida versatilis ), and adding culture medium (saccharified rice flour solution), on the metabolite profiles and microbial community of soy sauce produced from defatted soybean (DP) and whole soybean (HD). Relationships between microbes and volatiles, and their interactions, were shown. RESULTS: The dominant metabolites differed in the soy sauce samples except for isoflavones. Alcohols and phenols were higher in DP moromi. Two classes of dominant esters, long‐chain fatty acid esters (LFAE) and unsaturated‐short‐chain fatty acid esters (USFAE), were higher in HD moromi than DP. Weissella, Leuconostoc, and Aspergillus were the dominant microbes. Leuconostoc, and Aspergillus increased, and Weissella decreased in moromi inoculated with starters compared with a control. Similar changes to Leuconostoc were observed in moromi added culture medium. CONCLUSIONS: The microbes were responsible for the formation of volatiles. The intergeneric interactions with microbes were affected by fortified pattern. The effect of starters or culture medium on microbial community and metabolites of soy sauce depended on the raw material. © 2019 Society of Chemical Industry